알레르기 비염의 침 치료에 대한 체계적 고찰 - 문병권; 이유리; 조나경; 김경순; 최홍식; 김승모; Mun, Byeong-gwon; Lee, Yu-ri; Cho, Na-kyung; Kim, Kyung-soon; Choi, Hong-sik; Kim, Seung-mo (대한한방내과학회지, 2020)
Objectives: The purpose of this study was to assess the effects of acupuncture as a treatment for allergic rhinitis (AR). We used a meta-analysis and systematic review to analyze the results of randomized controlled trials (RCTs) that applied acupuncture to AR patients. Methods: The key question assessed the effects of acupuncture on patients with AR, and we included only RCTs. We searched the KoreaMed, NDSL, KMBASE, Koreantk, OASIS, PubMed, EMBASE, and Cochrane databases, with no language restriction. We assessed risk of bias with the Cochrane Risk of Bias tool. The random effects model was used to adjust for the heterogeneity of the included studies, and the effect sizes between two groups were reported as mean differences (MD) and risk ratios (RR). Results: Twelve RCTs were analyzed, with a total of 1788 participants; 824 participants were in the treatment group (i.e., acupuncture) and 964 were in the control group (sham acupuncture, western medicine, or waitlist). The meta-analysis results of 7 RCTs comparing the therapeutic efficacy of acupuncture with that of sham acupuncture showed a statistically significant difference (p<0.05) in the Rhinoconjunctivitis Quality of Life Questionnaire (RQLQ) and the Change of Total Nasal Symptom Score (TNSS). The meta-analysis of 4 RCTs comparing the therapeutic efficacy of acupuncture with western medicine showed statistically significant differences (p<0.05) in the RQLQ but not in the changes in effective rate (p>0.05). Conclusions: Acupuncture can be an effective treatment for AR, but more studies are required to enhance the level of evidence and to confirm safety.